Reduced treatment intensity in patients with early-stage Hodgkin's lymphoma - Engert, Andreas; Plütschow, Annette; Eich, Hans Theodor; Lohri, Andreas; Dörken, Bernd; Borchmann, Peter; Berger, Bernhard; Greil, Richard; Willborn, Kay C.; Wilhelm, Martin; Debus, Jürgen; Eble, Michael J.; et al. (The New England journal of medicine, 2010)
Radiation therapy was the original mainstay of treatment for patients who had early-stage Hodgkin's lymphoma with a favorable prognosis. With the use of such techniques as extended-field radiation therapy and total lymphoid irradiation, more than 80% of patients with localized disease became long-term survivors. However, the relapse rate with radiation therapy alone ranged from 20 to 40%,1-3 and extended-field radiation therapy and total lymphoid irradiation were associated with the occurrence of secondary solid tumors.4-8 The integration of a chemotherapy regimen consisting of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD)9 with radiation therapy resulted in greater efficacy and allowed the . . .